Aprendizagem para resiliência socioecológica de comunidades rurais: sistema de indicadores a partir de uma escola do campo - Oliveira, Maria Paula Pires de (Universidade Federal de São Carlos, 2022)
Socioecological resilience is related to the ability of a socioecological system to adapt to disturbances, in order to transform itself and still maintain its structure and function. Learning for resilience can contribute to strengthening communities from a perspective that recognizes the complexity and interdependence of the elements which compose socio-ecological systems. The objective of this research was to understand the role of school practices of an educational institution in the socio-ecological resilience of rural communities and the participatory process of definition, validation, application, and analysis of indicators established for this purpose. The research was carried out with the Terra Nova State School (Terra Nova do Norte, MT), a rural high school with technical qualification in agroecology whose work proposal is the pedagogy of alternation. The methodological strategy addressed intervention research and integrated qualitative and quantitative perspectives. At the school, workshops were held for conceptual alignment, as well as dynamics and the application of questionnaires to define, validate and apply the indicators in a participatory manner. Part of this work integrated an extension project with a continuing education course offering to fifteen professionals from the school. The proposition of the system of indicators involved bibliographical research and selection, coding and categorization of the data collected with the school. Four dimensions and fourteen indicators were defined, validated (3S method of self-validation, scientific validation and social validation), applied to students, former students, families and school staff and analyzed and discussed together with students and members of the school’s professional team. Among the school's contributions to socio-ecological resilience, environmental governance and adaptive co-management, are adaptive capacity, dialogue, experimentation, connection between school and territory, landscape diversification, collectivity, strengthening social bonds, valuing ecosystems and self-organization. The research brings as a scientific contribution the reflection on the socioecological resilience of rural communities and the role of the rural school in this context, as well as the development of a management tool (indicators) that can help the continuous improvement of school practices.

La resiliencia socioecológica está relacionada con la capacidad de un sistema socioecológico para adaptarse a las perturbaciones, con el fin de transformarse y aún mantener su estructura y función. El aprendizaje para la resiliencia puede contribuir al fortalecimiento de las comunidades desde una perspectiva que reconozca la complejidad e interdependencia de los elementos que componen los sistemas socioecológicos. El objetivo de esta investigación fue comprender el papel de las prácticas escolares en una institución educativa en la resiliencia socioecológica de comunidades rurales y el proceso participativo de definición, validación, aplicación y análisis de indicadores establecidos para este fin. La investigación se realizó con la Escuela Estadual Terra Nova (Terra Nova do Norte, MT), una escuela secundaria rural con formación técnica en agroecología cuya propuesta de trabajo es la pedagogía de la alternancia. La estrategia metodológica abordó la intervención-investigación e integró perspectivas cualitativas y cuantitativas. En la escuela se realizaron talleres de alineamiento conceptual, así como dinámicas y aplicación de cuestionarios para definir, validar y aplicar los indicadores de manera participativa. Parte de este trabajo formó parte de un proyecto de extensión que ofreció un curso de formación continua a quince profesionales de la escuela. La propuesta del sistema de indicadores involucró la investigación bibliográfica y la selección, codificación y categorización de los datos recolectados con la escuela. Cuatro dimensiones y catorce indicadores fueron definidos, validados (método 3S de autovalidación, validación científica y validación social), aplicados a alumnos, exalumnos, familias y personal del colegio y analizados y discutidos junto con alumnos y miembros del equipo profesional de la escuela. Entre los aportes de la escuela a la resiliencia socioecológica, la gobernanza ambiental y la cogestión adaptativa, se encuentran la capacidad adaptativa, el diálogo, la experimentación, la conexión entre la escuela y el territorio, la diversificación del paisaje, la colectividad, el fortalecimiento de los lazos sociales, la valoración de los ecosistemas y la autoorganización. La investigación trae como aporte científico una reflexión sobre la resiliencia socioecológica de las comunidades rurales y el papel de la escuela rural en este contexto, así como el desarrollo de una herramienta de gestión (indicadores) que puedan ayudar a la mejora continua de las prácticas escolares.
Learning for socioecological resilience of rural communities: indicator system proposal based on a rural school
Aprendizaje para la resiliencia socioecológica de comunidades rurales: sistema de indicadores desde una escuela rural
Keywords: Extensão universitária; Pedagogia da alternância; Sistemas socioecológicos; Educação do campo; Agroecologia; Governança ambiental; Cogestão adaptativa; University extension; Pedagogy of alternation; Socioecological systems; Rural education; Agroecology; Environmental governance; Adaptive co-management; Extensión universitaria; Pedagogía de la alternancia; Sistemas socioecológicos; Educación de campo; Agroecología; Gobernanza ambiental; Cogestión adaptativa; CIENCIAS EXATAS E DA TERRA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::AVALIACAO DE SISTEMAS, INSTITUICOES, PLANOS E PROGRAMAS EDUCACIONAIS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::ENSINO PROFISSIONALIZANTE